Contemporary practices of physical trainers in professional soccer: A qualitative study - Barrera-Díaz, Joel; Figueiredo, António J.; Field, Adam; Ferreira, Bruno; Querido, Sérgio M.; Silva, João Renato; Ribeiro, João; Pinto, Ismael; Cornejo, Patricio; Torres, Hernan; Saffa, Alvaro; Sarmento, Hugo (Frontiers in Psychology, 2023)
Physical trainers are integral for managing load, reducing injury and optimizing performance in professional soccer. However, little is known about how this practitioners operate in the applied setting and how some of the nuances experienced influence practice. This study explored the contemporary practices of physical trainers in professional soccer. Semi-structured interviews were undertaken with eight physical trainers from different professional teams in European and South American leagues. Interview questions were designed to extract information on the evaluation of physical abilities, monitoring and control of training and injury prevention. Subsequently, the interviews were video-recorded, transcribed, verbatim and analyzed using a content analysis approach. The results suggest that the evaluation of physical capacities is carried out by physical trainers at the beginning of the preseason. It also appears that it is attempted that this process of regular testing is applied during the competitive period, with most participants conducting partial physiological and physical evaluations at different stages throughout the competitive season. In relation to the monitoring and control of training, subjective feedback scales are used to estimate the internal load, and the use of GPS devices is common to quantify external loads. Injury prevention programmes were implemented by all participants and were generally in a multi-component format focused on preventing or optimizing physical capabilities. These insights can be used as a scientific reference point to inform applied practice in professional soccer, especially for practitioners that are inexperienced and aspiring to enhance how they operate in the field.